Epigenetic biomarkers for animal welfare monitoring - Whelan, Rose; Tönges, Sina; Böhl, Florian; Lyko, Frank (Frontiers in Veterinary Science, 2023)
Biomarkers for holistic animal welfare monitoring represent a considerable unmet need in veterinary medicine. Epigenetic modifications, like DNA methylation, provide important information about cellular states and environments, which makes them highly attractive for biomarker development. Up until now, much of the corresponding research has been focused on human cancers. However, the increasing availability of animal genomes and epigenomes has greatly improved our capacity for epigenetic biomarker development. In this review, we provide an overview about animal DNA methylation patterns and the technologies that enable the analysis of these patterns. We also describe the key frameworks for compound DNA methylation biomarkers, DNA methylation clocks and environment-specific DNA methylation signatures, that allow complex, context-dependent readouts about animal health and disease. Finally, we provide practical examples for how these biomarkers could be applied for health and environmental exposure monitoring, two key aspects of animal welfare assessments. Taken together, our article provides an overview about the molecular and biological foundations for the development of epigenetic biomarkers in veterinary science and their application potential in animal welfare monitoring.